2016
DOI: 10.1002/term.2114
|View full text |Cite
|
Sign up to set email alerts
|

VEGF released from a fibrin biomatrix increases VEGFR-2 expression and improves early outcome after ischaemia-reperfusion injury

Abstract: Skeletal ischaemia-reperfusion (I-R) injury may influence patient outcome after severe vascular trauma or clamping of major vessels. The aim of this study was to observe whether locally applied vascular endothelial growth factor (VEGF) in fibrin could induce the expression of VEGF-receptor-2 (VEGFR-2) and improve the outcome after I-R injury. Transgenic mice expressing VEGFR-2 promoter-controlled luciferase were used for the assessment of VEGFR-2 expression. Ischaemia was induced for 2 h by a tension-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Inflammatory mediators, such as ICAM and VCAM, block the microvessels and lead to activation of leukocytes to release inflammatory mediators. These mediators can also release a large amount of oxygen free radicals [ 22 , 23 ]. What is more, ICAM and VCAM are the mediators after the stimulation of TNF- α , IL-1, and endotoxin, leading to adhesion, aggregation, rolling, and exudation of leukocytes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory mediators, such as ICAM and VCAM, block the microvessels and lead to activation of leukocytes to release inflammatory mediators. These mediators can also release a large amount of oxygen free radicals [ 22 , 23 ]. What is more, ICAM and VCAM are the mediators after the stimulation of TNF- α , IL-1, and endotoxin, leading to adhesion, aggregation, rolling, and exudation of leukocytes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Annette et al [ 23 ] found that, in the process of oxidative stress, the amount of xanthine oxidase would be enhanced significantly. The xanthine oxidase (XO) could break down hypoxanthine and xanthine to uric acid and release superoxide, which is consistent with our experimental result.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological process of ischemia-reperfusion injury is complicated, with potent roles played by oxidative stress response and acute inflammatory response [ 5 , 6 ]. Inflammatory mediators, such as intracellular adhesion molecule-1 (ICAM-1) and tumor necrosis factor-α (TNF-α), can aggravate and block micro-vessels, further leading to the release of inflammatory mediators and cytokines by activating leukocytes, and exerting secondary neuron damage under the direction of oxygen free radicals [ 7 , 8 ]. Nuclear factor kappa B (NF-κB) has pluripotent modulatory roles, and can modulate gene expression levels of various inflammatory mediators, cytokines, and chemotactic factors such as interleukn-8 (IL-8), IL-6, and ICAM, thus playing an important role in cell inflammation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were similar to the literature review by Foroglou et al 6 It showed an association of ASCs increased the vascular density and the surgical flap viability and cytokines (Vegf-a). In addition, Moritz et al 17 injected Vegf in surgical flaps submitted to ischemia-reperfusion and compared it with placebo. This experiment showed the positive effect of the Vegf-a cytokine on the viability of ischemic surgical flap 10 .…”
Section: Discussionmentioning
confidence: 99%